Prefabricated breathable coiled material and preparation method thereof
By adding calcium sulfate whiskers and calcium sulfate powder to the prefabricated coil and using punching and spacer coating technology, the moisture reflux and foaming problems of the coil are solved, improving its wear resistance and mechanical properties, and extending its use Lifespan and reduce costs.
Patent Information
- Application Number
- CN202411683283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
During use, prefabricated coils are prone to reflux and bubbles due to evaporation of underground water vapor, which affects their service life and performance.
The design of prefabricated breathable coils is improved by adding calcium sulfate whiskers and calcium sulfate powder to the surface and bottom layers, combining SEBS and polypropylene materials, and improving the wear resistance and mechanical properties of the coils, and through hole punching and spacement Adhesive glue improves breathability.
It effectively prevents the reflux and foaming problems caused by ground air from the coil, extends the service life, and improves the wear resistance and mechanical properties of the coil, and reduces costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a prefabricated breathable coiled material and a preparation method thereof. Background Art
[0002] As an emerging high-performance material, prefabricated coils are gradually becoming the first choice for sports facility construction. It not only improves the safety and comfort of sports venues, but also leads the innovation trend of sports venue materials with its unique advantages. Prefabricated coils are prefabricated in factories through precise production processes. The materials have excellent elasticity and shock absorption properties, can effectively absorb the impact force during exercise, reduce the risk of injury to athletes, and are especially suitable for high-intensity competitive sports, providing athletes with a safe sports environment. Prefabricated coils are suitable for track and field competition venues and training venues at all levels, as well as for various school competitions and teaching venues. However, since the coils are laid on the ground, the evaporation of water vapor underground will make the coils easy to get damp and bubble, thereby affecting the use and life of the coils. Therefore, it is necessary to prepare a breathable coil to prevent moisture and bubbling caused by ground air and extend the service life of the coils. Summary of the invention
[0003] The present invention provides a prefabricated breathable coiled material and a preparation method thereof, which solves the problems of poor air permeability, wear resistance and mechanical properties of the prefabricated coiled material in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a prefabricated breathable coiled material, which comprises a surface layer and a bottom layer from top to bottom, wherein the surface layer comprises the following raw materials in parts by weight: 30-40 parts of SEBS, 15-22 parts of polypropylene, 15-25 parts of a first filler, 25-30 parts of a softener, 1-3 parts of an antioxidant, and 1-3 parts of maleic anhydride grafted polypropylene; The bottom layer comprises the following raw materials in parts by weight: 15-22 parts of SEBS, 30-40 parts of polypropylene, 20-30 parts of a second filler, 25-30 parts of a softener, and 1-3 parts of maleic anhydride grafted polypropylene; The first filler and the second filler are both calcium-containing compounds.
[0005] As a further technical solution, the first filler and the second filler are each independently one or more of calcium carbonate, calcium sulfate, and calcium oxide.
[0006] As a further technical solution, the first filler and the second filler are both calcium sulfate.
[0007] In the present invention, calcium sulfate is added to the prefabricated coiled material, thereby improving the impact resistance, toughness and strength of the prefabricated coiled material.
[0008] As a further technical solution, the first filler and the second filler each independently include one or both of calcium sulfate whiskers and calcium sulfate powder.
[0009] As a further technical solution, the first filler is composed of calcium sulfate whiskers and calcium sulfate powder, and the second filler is calcium sulfate powder.
[0010] In the present invention, calcium sulfate whiskers and calcium sulfate powder are added to the surface layer to improve the wear resistance, elasticity and tensile properties of the surface layer, and calcium sulfate powder is added to the bottom layer to improve the density and wear resistance of the bottom layer, further improving the wear resistance and mechanical properties of the prefabricated coil.
[0011] As a further technical solution, the mass ratio of calcium sulfate whiskers to calcium sulfate powder in the first filler is 3-5:1.
[0012] In the present invention, by limiting the mass ratio of calcium sulfate whiskers to calcium sulfate powder in the first filler to 3-5:1, the wear resistance and tensile strength of the prefabricated coil are further improved.
[0013] As a further technical solution, the mass ratio of calcium sulfate whiskers to calcium sulfate powder in the first filler is 4:1.
[0014] As a further technical solution, the diameter of the calcium sulfate whisker is 25-37 μm, and the aspect ratio is 37.
[0015] As a further technical solution, the particle size of the calcium sulfate powder is 1250 mesh.
[0016] As a further technical solution, the softener includes one or more of cyclohexane oil, polyethylene wax, and aromatic oil.
[0017] As a further technical solution, the antioxidant includes one or more of antioxidant 1010 , antioxidant 168 , and antioxidant 1330 .
[0018] As a further technical solution, the surface layer also includes 1 to 5 parts of polytetramethylene ether glycol.
[0019] As a further technical solution, the number average molecular weight of the polytetrahydrofuran ether diol is 1000-1800.
[0020] As a further technical solution, the mass ratio of maleic anhydride grafted polypropylene to polytetramethylene ether glycol in the surface layer is 1:2-4.
[0021] As a further technical solution, the mass ratio of maleic anhydride grafted polypropylene to polytetramethylene ether glycol in the surface layer is 1:3.
[0022] In the present invention, polytetramethylene glycol and maleic anhydride grafted polypropylene are added to the surface layer for compounding, thereby further improving the tensile strength and abrasion resistance of the prefabricated coiled material.
[0023] The present invention also provides a method for preparing a prefabricated breathable coiled material, comprising the following steps: The raw materials of the surface layer and the bottom layer are mixed evenly, and then extruded and hot-pressed to obtain a prefabricated breathable coiled material.
[0024] As a further technical solution, the preparation method of the prefabricated breathable coiled material is: after the raw materials of the surface layer and the bottom layer are uniformly mixed, the prefabricated breathable coiled material is obtained by extrusion, hot pressing, embossing, cooling and punching.
[0025] As a further technical solution, the thickness of the surface layer is 2-5 mm, and the thickness of the bottom layer is 5-10 mm.
[0026] As a further technical solution, the extrusion temperature is 180-220°C.
[0027] The present invention also provides an application of a prefabricated breathable coiled material, which is to apply glue to the bottom layer of the prefabricated breathable coiled material and then stick it on the ground. The specific method of applying glue is: longitudinally: apply glue every 30 centimeters; transversely: leave a drainage hole every 1 meter, and the width of the drainage hole is 10 centimeters.
[0028] In the present invention, holes are punched on the coiled material and glue is applied at intervals, thereby improving the air permeability of the prefabricated coiled material and solving the problem that the coiled material is susceptible to moisture and blistering due to the influence of ground air.
[0029] The working principle and beneficial effects of the present invention are: In the present invention, the prefabricated coiled material is composed of a surface layer and a bottom layer, and the base materials of the surface layer and the bottom layer are both composed of SEBS and polypropylene, but the contents of SEBS and polypropylene in the surface layer and the bottom layer are different, which not only improves the wear resistance and mechanical properties of the prefabricated coiled material, but also reduces the cost of the prefabricated coiled material; and by adding calcium-containing compounds to the surface layer and the bottom layer to form physical entanglement with SEBS and polypropylene, the wear resistance and mechanical properties of the prefabricated coiled material are further improved, and the problem of poor wear resistance and mechanical properties of the prefabricated coiled material is solved. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following embodiments and comparative examples: SEBS, model: G1701; polypropylene, model: K8303; cyclohexane oil, model: N4010; polyethylene wax, model: Q-18PE; aromatic oil, kinematic viscosity: 25~50; maleic anhydride grafted polypropylene, model: B1-1; polytetramethylene ether glycol, number average molecular weight 1000, 1400, 1800; calcium sulfate whisker, diameter 25~37μm, aspect ratio 37; calcium sulfate powder, particle size 1250 mesh; calcium carbonate, particle size 1250 mesh; calcium oxide, particle size 1250 mesh.
[0032] Example 1 A method for preparing a prefabricated breathable coiled material comprises the following steps: Raw materials of the surface layer components by weight: 30 parts of SEBS, 15 parts of polypropylene, 15 parts of calcium carbonate (1250 mesh), 25 parts of naphthenic oil, 1 part of antioxidant 1010, 1 part of maleic anhydride grafted polypropylene; The raw materials of the bottom layer components by weight are: 15 parts of SEBS, 30 parts of polypropylene, 20 parts of calcium carbonate (1250 mesh), 25 parts of naphthenic oil, and 1 part of maleic anhydride grafted polypropylene; The raw materials of the surface layer and the bottom layer are mixed uniformly, extruded at 180° C., hot pressed, embossed, cooled and punched to obtain a prefabricated breathable coiled material; wherein the thickness of the surface layer is 2 mm, and the thickness of the bottom layer is 5 mm.
[0033] Example 2 A method for preparing a prefabricated breathable coiled material comprises the following steps: Raw materials of the surface layer components by weight: 35 parts of SEBS, 18 parts of polypropylene, 20 parts of calcium oxide (1250 mesh), 27 parts of polyethylene wax, 2 parts of antioxidant 168, 2 parts of maleic anhydride grafted polypropylene; The raw materials of the bottom layer components by weight are: 18 parts of SEBS, 35 parts of polypropylene, 25 parts of calcium oxide (1250 mesh), 27 parts of polyethylene wax, and 2 parts of maleic anhydride grafted polypropylene; The raw materials of the surface layer and the bottom layer are mixed uniformly, extruded, hot pressed, embossed, cooled and punched at 200° C. to obtain a prefabricated breathable coiled material; the thickness of the surface layer is 3 mm, and the thickness of the bottom layer is 8 mm.
[0034] Example 3 A method for preparing a prefabricated breathable coiled material comprises the following steps: Raw materials of the surface layer components by weight: 40 parts of SEBS, 22 parts of polypropylene, 25 parts of calcium sulfate powder (1250 mesh), 30 parts of aromatic oil, 3 parts of antioxidant 168, 3 parts of maleic anhydride grafted polypropylene; Raw materials of the bottom layer components by weight: 22 parts of SEBS, 40 parts of polypropylene, 30 parts of calcium sulfate powder (1250 mesh), 30 parts of aromatic oil, 3 parts of maleic anhydride grafted polypropylene; The raw materials of the surface layer and the bottom layer are mixed uniformly, extruded, hot pressed, embossed, cooled and punched at 220° C. to obtain a prefabricated breathable coiled material; wherein the thickness of the surface layer is 5 mm, and the thickness of the bottom layer is 10 mm.
[0035] Example 4 The only difference between this embodiment and embodiment 1 is that the calcium carbonate (1250 mesh) in the surface layer and the bottom layer is replaced by an equal amount of calcium sulfate powder (1250 mesh).
[0036] Example 5 The only difference between this embodiment and embodiment 1 is that the calcium carbonate (1250 mesh) in the surface layer and the bottom layer is replaced by an equal amount of calcium sulfate whiskers (with a diameter of 25-37 μm and an aspect ratio of 37).
[0037] Example 6 The only difference between this embodiment and embodiment 4 is that the calcium sulfate powder (1250 mesh) in the surface layer is replaced with an equal amount of calcium sulfate powder (300 mesh) and calcium sulfate whiskers (diameter of 25-37 μm, aspect ratio of 37) in a mass ratio of 1:3.
[0038] Example 7 The only difference between this embodiment and embodiment 4 is that the calcium sulfate powder (1250 mesh) in the surface layer is replaced with an equal amount of calcium sulfate powder (1250 mesh) and calcium sulfate whiskers (diameter 25-37 μm, aspect ratio 37) in a mass ratio of 1:4.
[0039] Example 8 The only difference between this embodiment and embodiment 4 is that the calcium sulfate powder (1250 mesh) in the surface layer is replaced with an equal amount of calcium sulfate powder (1250 mesh) and calcium sulfate whiskers (diameter 25-37 μm, aspect ratio 37) in a mass ratio of 1:5.
[0040] Example 9 The only difference between this embodiment and embodiment 7 is that 5 parts of polytetramethylene glycol (number average molecular weight is 1000) are added to the surface layer.
[0041] Example 10 The difference between this embodiment and embodiment 7 is that 5 parts of polytetramethylene glycol (number average molecular weight is 1400) are added to the surface layer.
[0042] Embodiment 11 The difference between this embodiment and embodiment 7 is that 5 parts of polytetramethylene glycol (number average molecular weight is 1800) are added to the surface layer.
[0043] Example 12 The only difference between this embodiment and embodiment 9 is that 1 part of polytetramethylene glycol (number average molecular weight is 1400) is added to the surface layer.
[0044] Embodiment 13 The difference between this embodiment and embodiment 9 is that 2 parts of polytetramethylene glycol (number average molecular weight is 1400) are added to the surface layer.
[0045] Embodiment 14 The only difference between this embodiment and embodiment 9 is that 3 parts of polytetramethylene glycol (number average molecular weight is 1400) are added to the surface layer.
[0046] Embodiment 15 The only difference between this embodiment and embodiment 9 is that 4 parts of polytetramethylene glycol (number average molecular weight is 1400) are added to the surface layer.
[0047] Comparative Example 1 The only difference between this comparative example and Example 1 is that the calcium carbonate (1250 mesh) in the surface layer and the bottom layer is replaced by an equal amount of silicon dioxide (1250 mesh).
[0048] The wear resistance and mechanical properties of the prefabricated breathable coils prepared in Examples 1 to 15 and Comparative Example 1 were tested respectively, and the specific measuring methods are as follows: Wear resistance: The wear resistance is tested in accordance with GB / T 14833-2020 "Synthetic material sports field surface layer"; Mechanical properties: Tensile strength test according to EN 14810-2006 "Sports surfaces - Determination of spike resistance"; The test results are shown in Table 1.
[0049] Table 1 Prefabricated breathable membrane performance test results
[0050] Compared with Example 1, the filler in Comparative Example 1 is silicon dioxide. As a result, the abrasion loss of the prefabricated breathable coil prepared in Comparative Example 1 is higher than that in Example 1, and the tensile strength is lower than that in Example 1, indicating that the calcium compound filler can improve the wear resistance and mechanical properties of the prefabricated breathable coil.
[0051] Compared with Example 1, the composition of the filler in the surface layer and the bottom layer is changed in Examples 4 to 8, and the wear amount of the prefabricated breathable coil prepared in Example 5 is lower than that in Examples 1 and 4, and the tensile strength is higher than that in Examples 1 and 4, indicating that the use of calcium sulfate whiskers as fillers can further improve the wear resistance and mechanical properties of the prefabricated breathable coil; compared with Examples 6 to 8, the mass ratio of calcium sulfate whiskers and calcium sulfate powder in the surface layer is changed, and the wear amount of the prefabricated breathable coil prepared in Examples 6 to 8 is lower than that in Examples 4 and 5, and the tensile strength is higher than that in Examples 4 and 5, indicating that when the mass ratio of calcium sulfate whiskers and calcium sulfate powder in the surface layer is 3 to 5:1, the wear resistance and mechanical properties of the prefabricated breathable coil can be further improved; and the wear amount of the prefabricated breathable coil prepared in Example 7 is lower than that in Examples 6 and 8, and the tensile strength is higher than that in Examples 6 and 8, indicating that when the mass ratio of calcium sulfate whiskers and calcium sulfate powder in the surface layer is 4:1, the wear resistance and mechanical properties of the prefabricated breathable coil can be further improved.
[0052] Compared with Example 7, Examples 9 to 11 added polytetramethylene glycol with different number average molecular weights to the surface layer. As a result, the abrasion of the prefabricated breathable coil prepared in Example 10 was lower than that in Examples 9 and 11, and the tensile strength was higher than that in Examples 9 and 11, indicating that when the number average molecular weight of polytetramethylene glycol is 1400, the wear resistance and mechanical properties of the prefabricated breathable coil can be further improved.
[0053] Compared with Example 10, Examples 12 to 15 change the amount of polytetrahydrofuran ether glycol added, and as a result, the prefabricated breathable coiled materials prepared in Examples 13 to 15 have a lower abrasion amount than Examples 10 and 12, and a higher tensile strength than Examples 10 and 12, indicating that when the mass ratio of maleic anhydride grafted polypropylene to polytetrahydrofuran ether glycol in the surface layer is 1:2 to 4, the wear resistance and mechanical properties of the prefabricated breathable coiled materials can be further improved; by comparing Examples 13 to 15, it is found that the prefabricated breathable coiled materials prepared in Example 14 have a lower abrasion amount than Examples 13 and 15, and a higher tensile strength than Examples 13 and 15, indicating that when the mass ratio of maleic anhydride grafted polypropylene to polytetrahydrofuran ether glycol in the surface layer is 1:3, the wear resistance and mechanical properties of the obtained prefabricated breathable coiled materials are the highest.
[0054] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A prefabricated breathable coiled material, characterized in that: From top to bottom, there are a surface layer and a bottom layer, wherein the surface layer comprises the following raw materials in parts by weight: 30-40 parts of SEBS, 15-22 parts of polypropylene, 15-25 parts of a first filler, 25-30 parts of a softener, 1-3 parts of an antioxidant, and 1-3 parts of maleic anhydride grafted polypropylene; The bottom layer comprises the following raw materials in parts by weight: 15-22 parts of SEBS, 30-40 parts of polypropylene, 20-30 parts of a second filler, 25-30 parts of a softener, and 1-3 parts of maleic anhydride grafted polypropylene; The first filler and the second filler are both calcium-containing compounds.
2. A prefabricated breathable coiled material according to claim 1, characterized in that: The first filler and the second filler are each independently one or more of calcium carbonate, calcium sulfate, and calcium oxide.
3. A prefabricated breathable coiled material according to claim 2, characterized in that: The first filler and the second filler are both calcium sulfate.
4. A prefabricated breathable coiled material according to claim 3, characterized in that: The first filler and the second filler each independently include one or both of calcium sulfate whiskers and calcium sulfate powder.
5. The prefabricated breathable coiled material according to claim 1, characterized in that: The softener includes one or more of naphthenic oil, polyethylene wax and aromatic oil.
6. The prefabricated breathable coiled material according to claim 1, characterized in that: The surface layer also includes 1 to 5 parts of polytetramethylene ether glycol.
7. A prefabricated breathable coiled material according to claim 6, characterized in that: The number average molecular weight of the polytetramethylene ether diol is 1000-1800.
8. The prefabricated breathable coiled material according to claim 6, characterized in that: The mass ratio of maleic anhydride grafted polypropylene to polytetramethylene ether glycol in the surface layer is 1:2-4.
9. A method for preparing a prefabricated breathable coiled material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials of the surface layer and the bottom layer are mixed evenly, and then extruded and hot-pressed to obtain a prefabricated breathable coiled material.
10. The method for preparing a prefabricated breathable coiled material according to claim 9, characterized in that: The extrusion temperature is 180-220°C.
Citation Information
Patent Citations
Recyclable prefabricated runway as well as preparation method and recycling method thereof
CN113817309A
Prefabricated plastic track with scaly surface and preparation method thereof
CN116334975A
Polypropylene composition as well as preparation method and application thereof
CN117986750A
use of THERMOPLASTIC COMPOSITIONS BASED ON FUNCTIONALIZED POLYOLEFINS GRAFTED BY POLYETHER PATTERNS TO PRODUCE WATERPROOF-BREATHABLE MATERIALS AND THEIR APPLICATIONS
FR2897356A1
Single-layer roof waterproof coiled material and preparation method therefor
WO2017066990A1